Electrically conducting collagen and collagen–mineral composites for current stimulation1. Issue 71 (2nd August 2015) - Kumar, M. Ramesh; Freund, Michael S.
<x xml:space="preserve">Abstract</x> Electrochemical aggregation of (a) collagen–PEDOT:PSS and (b) collagen–calcium phosphate–PEDOT:PSS.